2015
DOI: 10.1371/journal.pone.0136271
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Brain Disorders: Towards a ‘Horizontal Epidemiology’ of Psychosocial Difficulties and Their Determinants

Abstract: ObjectiveTo test the hypothesis of ‘horizontal epidemiology’, i.e. that psychosocial difficulties (PSDs), such as sleep disturbances, emotional instability and difficulties in personal interactions, and their environmental determinants are experienced in common across neurological and psychiatric disorders, together called brain disorders.Study DesignA multi-method study involving systematic literature reviews, content analysis of patient-reported outcomes and outcome instruments, clinical input and a qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 43 publications
(46 reference statements)
4
31
0
Order By: Relevance
“…This is consistent with an earlier UK general practice study, where 47% of 192 participants reported some degree of negative emotional impact within 3 years of diagnosis [37]. Another European study indicated that 74% of those with epilepsy had some emotional difficulties reported on the WHODAS [29]. Evidence based upon eight randomized control trials showed that psychological treatments (i.e.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This is consistent with an earlier UK general practice study, where 47% of 192 participants reported some degree of negative emotional impact within 3 years of diagnosis [37]. Another European study indicated that 74% of those with epilepsy had some emotional difficulties reported on the WHODAS [29]. Evidence based upon eight randomized control trials showed that psychological treatments (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…The SEISMIC WHODAS-12 average total score at diagnosis was comparable with normative Australia data [31], showing that people with a physical disorder have scores (mean ± SD 4.3 ± 6.1) lower than those with mental health disorders, but higher than those free of any health problems (although, epilepsy and other neurological conditions were not included as physical disorders in that study). The SEISMIC data are also comparable to results of a study of people with a variety of brain disorders: similar proportions of people with epilepsy had problems with daily work, concentration, learning, activities, mobility and household tasks [29]. However, the frequency of our participants reporting disability was lower than in people with spinal cord injury [32], multiple sclerosis [29], Parkinson`s disease [29], mental illness [29,33], and substance abuse [33].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Dementia impairs quality of life and life expectancy in advanced stages, causing grave emotional and economic impact on patients and their caregivers . There is no known cure for dementia .…”
Section: Introductionmentioning
confidence: 99%